SIMULATION OF USE AND MANAGEMENT EFFECTS ON THE SOIL ORGANIC MATTER POOLS OF THE ATLANTIC FOREST BIOME, BRAZIL - Wendling, Beno; Jucksch, Ivo; Mendonca, Eduardo de Sa; Almeida, Risely Ferraz de [UNESP]; Martins, Carlos Eugenio; Silva Domingues, Luis Augusto da (Univ Federal Uberlandia, 2014)
Soil organic matter simulation in areas under long term use provides an important tool to test future scenarios, enabling the adoption of less impressive management to environment. The purposes of the present study were: a) to simulate, with the Century model, the impacts on soil organic matter, according to the adoption of different crop management, with forage purposes, in two different soils and; b) to validate the Century model for these managements and soils by comparing the simulated values with those measured in the field. The following treatments were evaluated: in the Oxisol area - brachiaria pasture with fertilizer (BPw) and without fertilizer (BPwo), the Incept area - corn for silage (CS), Coast Cross pasture (CC) and sugar cane field (SC). The microbial biomass represented the active compartment of carbon and nitrogen, the particle free light fraction represented the slow compartment of carbon and nitrogen and the passive pools were determined by the difference of the total minus the active and the slow pools (passive = total - (active + slow)). The Century model showed great potential to simulate the dynamics of the total C and N stocks for tropical soils, which was confirmed by similarity between the simulated values and those measured in the field.
Keywords: Century model; Carbon; Nitrogen; Tropical soils